The ethylene receptor ETR1 is required for Fusarium oxysporum pathogenicity - Pantelides, Iakovos S; Tjamos, Sotirios E.; Pappa, S.; Kargakis, Μ.; Paplomatas, Epaminondas J. (My University, 2013)
Fusarium oxysporum is a ubiquitous vascular wilt plant pathogen causing severe yield losses in a wide range of economically important crops. In this study, the interaction between Fusarium oxysporum f. sp. raphani and Arabidopsis thaliana plants impaired in the salicylate (SA), jasmonate (JA) and ethylene (ET) defence signalling pathways was investigated to better understand the nature of this plant-microbe interaction. The in planta bioassays revealed a key role for the ETR1 receptor as the etr1-1 mutant plants exhibited statistically less Fusarium wilt symptoms compared to the other mutant and Col-0 plants. Quantitative polymerase chain reaction (qPCR) analysis associated the decrease in symptom severity shown in etr1-1 plants with reduced vascular growth of the pathogen, suggesting the activation of defence mechanisms in etr1-1 plants against F. oxysporum. Furthermore, the early activation and increased accumulation of the SA-responsive PR1, PR2 and PR5 genes in the etr1-1 plants, in contrast to the Col-0 plants that showed higher transcript levels of the JA/ET-responsive PR3, PR4 and PDF1.2 genes after F. oxysporum inoculation, can lead to speculation that F. oxysporum hijacks ETR1-mediated ethylene signalling to promote disease development in plants.
Keywords: Arabidopsis; Fusarium oxysporum f. sp. raphani; Vascular wilts; Plant defence